2016
DOI: 10.1002/zoo.21294
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein on serum metabolites and antioxidant status: A study in Chrysolophus amherstiae

Abstract: This experiment was conducted to study the effect of feeding graded levels of dietary crude protein (CP) on serum biochemical profile of Lady Amherst's pheasants (LAP). Eighteen male LAP were randomly distributed into three groups of six each in an experiment based on completely randomized design. The CP content of the diets was 13.4%, 16.5%, and 19.1%, in groups I, II, and III, respectively. Serum concentrations of uric acid was lowest (P < 0.05) in group I. Relationship between serum concentration of uric ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Besides, the antioxidant capacity has been indicated to be associated with meat quality traits ( 20 ). A previous study showed that a dietary lower methionine and cysteine ratio in an LP diet improved antioxidant capacity in boar ( 38 ), while the extreme LP diet might not support well the antioxidant defense and ability to combat the stress in Chrysolophus amherstiae ( 39 ). Here, we also found that the LP diets reduced plasma MDA contents and increased the GSH contents in the plasma of finishing pigs.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, the antioxidant capacity has been indicated to be associated with meat quality traits ( 20 ). A previous study showed that a dietary lower methionine and cysteine ratio in an LP diet improved antioxidant capacity in boar ( 38 ), while the extreme LP diet might not support well the antioxidant defense and ability to combat the stress in Chrysolophus amherstiae ( 39 ). Here, we also found that the LP diets reduced plasma MDA contents and increased the GSH contents in the plasma of finishing pigs.…”
Section: Discussionmentioning
confidence: 98%